The role of omega-3 fatty acids in alleviating symptoms of dysmenorrhea - Marlena Cąkała; Joanna Skotnicka; Maria Witkowska; Magdalena Kozioł; Kamila Podgórniak; Aleksandra Zajkowska (Nicolaus Copernicus University in Toruń, 2024)
Introduction: The study will focus on presenting the effects of adequate intake or supplementation of omega-3 fatty acids on patients' perception of menstrual pain. Other known characteristics of these substances will also be presented. Aim of the study: The aim of the study was to demonstrate impact of omega-3 fatty acids supplementation or normal supply to dysmenorrhea among women through a literature review. State of Knowledge: Dysmenorrhea is a condition that limits normal functioning and affects up to 90% of women. Therefore, it is so important to study its pathogenesis and prevent its occurrence. It results in the use of painkillers and the absence of many women from daily activities. Omega-3 acids are polyunsaturated fatty acids that have a positive effect on numerous organs and functions of the human body. They are substances with anti-inflammatory properties, which have been used in research on the influence of omega-3 acids on reducing dysmenorrhea among women. Conclusion: Omega-3 acids reduce dysmenorrhea in women. It is very important to pay attention to the presence of acids in diet as well as supplementation among patients.